Automatic periodic stimulation of the vagus nerve during single‐incision transaxillary robotic thyroidectomy: Feasibility, safety, and first cases. Issue 3 (5th November 2015) - Lörincz, Balazs B.; Möckelmann, Nikolaus; Busch, Chia‐Jung; Hezel, Markus; Knecht, Rainald
Abstract: Background: Automatic periodic stimulation (APS) of the vagus nerve during thyroid surgery may provide the patient with increased safety to prevent impending thermal or stretch‐related injury to the recurrent laryngeal nerve (RLN). Methods: Vagal stimulation would be of particular interest in remote access robotic thyroid surgery, where the RLN may be exposed to more conducted heat because of the exclusive use of the Harmonic scalpel. Using APS, the console surgeon may adjust the dissection technique according to the signal changes to avoid impending thermal damage to the nerve. Results: In 2 transaxillary robotic thyroidectomy cases, we placed the vagus electrode onto the ipsilateral vagus trunk through the single‐incision transaxillary access before docking the da Vinci robot. APS of the ipsilateral nerve has been conducted without complications. Conclusion: APS of the ipsilateral vagus is feasible and safe during transaxillary robotic thyroidectomy, and may contribute to prevent impending thermal injury to the RLN. © 2015 Wiley Periodicals, Inc. Head Neck 38: 482–485, 2016